Evaluating User Experience in 3D Interaction: A Systematic Review - Veriscimo, Erico de Souza; Bernardes Júnior, João Luiz; Digiampietri, Luciano Antonio (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2020)
Modern Information Systems often produce or utilize large sets of complex, multivariate data and, while understanding and visualizing this data can be of critical importance, particularly to support decision-making, it is frequently a challenging task. Information Visualization techniques exist to aid in this task and often take advantage of tridimensional visualizations and animations to explore complex data. But users may also find that difficult or intimidating and, according to the Technology Acceptance Model, they must judge such 3D information visualization favorably regarding not only perceived usefulness but also perceived ease-of-use before adopting it. Therefore, User Experience is critical for the acceptance and use of these tools. And a more natural way to interact in this domain are 3D Interfaces, which are also increasingly coming to market in several areas such as education, entertainment, health, large-display or automotive interaction, etc, even though there is still a gap in the literature regarding the evaluation of User Experience in 3D Interaction. This paper presents a Systematic Literature Review to identify, compare and offer a critical analysis of the main methods, tools, and metrics used to evaluate User Experience in 3D Interaction in Information Systems. Our search string returned 158 unique papers from IEEE and ACM repositories, out of which 44 were selected based on the first filtering with inclusion and exclusion criteria and 34 remained after the second filtering. Questionnaires were the most frequently used tool, not all standardized, and several different criteria related to emotions or performance were evaluated.